Moisture effects on the bond strength of FRP-masonry elements - Ghiassi, Bahman (2012)
Moisture exposure has been observed to be one of the degrading environmental agents which affects the durability of the FRP-strengthened elements by changing the constituent material or bond properties. This paper presents the experimental investigation on the effects of moisture on the pull-off bond strength of GFRP-strengthened brick specimens. The specimens have been prepared following the wet lay-up procedure and exposed to constant moisture level of 100% R.H. at 23̊C for 8 weeks. The degradation in the bond performance has been investigated by performing pull-off tests on the conditioned specimens after 4 and 8 weeks of exposure. The reversibility of the bond degradation has been also studied by storing some specimens in the laboratory conditions for 1 week after conditioning and before performing the pull-off tests. Comparative analysis has been performed and the main results are presented and discussed.